Female Artists, Past and Present. - Hill, Vicki Lynn (Berkeley : Women's History Research Center Inc., 1974)
Contents: Female Artists in Art History ; Individual Women Artists Practicing Today ; Women Working in Other Areas of the Visual Arts ; The Contemporary Female Artists Movement ; ...
Engels
boek